Allelopathic effects of saffron (Crocus sativus L.) on germination and seedling growth characteristics of wild barley (Hordeum spontaneum) and couch grass (Agropayron repense) - Mahdi Ghesmati; Mohammed Hossein Aminifard; Masume Abdollahi; Masume Shakeri (Zirā̒at va Fanāvarī-i Za̒farān, 2018)
In order to evaluate the allelopathic effects of saffron (Crocus sativus L.) corm and leaf aqueous solution on germination characteristics and preliminary growth of weed species including wild barley (Hordeum spontaneum) and couch grass (Agropayron repense) two separate experiments for each species were conducted at the research laboratory of the School of Agriculture of the University of Birjand in 2016. A factorial experiment in a completely randomized design with three replications was conducted for each species. The factors included saffron organs at two levels (leaves and corms) and water extract concentrations at 5 levels (0, 0.5, 1, 1.5 and 2 percent). The results indicated that the lowest seed germination percentage of wild barley and couch grass were observed at a concentration of 2% of leaf and concentration of 2% of corm, respectively. The results indicated that the lowest rate of germination of wild barley and couch grass were observed at a concentration of 2% of leaf and corm extract, respectively. Different concentrations of leaf and corm extracts significantly decreased the length of radicle, seedling fresh weight and seedling dry weight of two weeds. The logistic model provided a successful estimation of the relationship between leaf water extract and germination percentage of two weeds. Based on orthogonal comparison tests, the allelopathic inhibitory effects of saffron leaves and corms were the same for two weeds. The results showed that leaf extract of saffron the most influence on wild barley and corm extract of saffron the best effect on couch grass. Therefore, results of this study, confirm that can be used the allelopathic effects of saffron to reduce these two weeds in the field.